Evolutionary development of labor competencies: a review of the literature - Estrella-Cardenas, Salma Y. (2022)
Objective. To identify the theoretical approaches on labor competencies in the period 2010-2021. Methodology. This research is a review article that uses as a tool the PRISMA 2009 Protocol, by means of which it was possible to select the articles according to certain criteria such as inclusion and exclusion. Results. The study conducted on labor competencies showed that during the period 2010-2021, the number of review articles increased considerably, of which 35 articles that passed through various filters were taken into account. Conclusion. It was possible to appreciate the existence of a greater elaboration of research between 2019 and 2020, giving greater emphasis to this variable, since the construct of labor competencies reveals a whole set of knowledge, skills, attitudes and experiences that determine the execution of a successful task.